Tourism Development Strategy for Increasing Local OwnSource Revenue in Kupang City During the COVID-19 Pandemic - Anisetuf A. A.W. Wasonono; Nikson Tameno; Aldarine Molidya (Penerbit Goodwood, 2025)
Purpose: This study examines how the Kupang City Tourism Office formulated strategy to increase Local Own-Source Revenue (LO-SR) or Pendapatan Asli Daerah (PAD) during the COVID-19 pandemic and identifies the internal and external barriers encountered in that process.Methodology: A qualitative case study design was applied, combining semi-structured interviews with five key informants from the Tourism Office and Regional Revenue Office with secondary documentary data, analysed through SWOT-based IFAS and EFAS matrices.Results: Kupang City tourism was positioned in Quadrant I (IFAS = 2.31; EFAS = 1.96), indicating that an aggressive, growth-oriented (S-O) strategy is appropriate, centred on integrated destination management, certified human resource development, and cultural heritage optimisation; however, PAD contributions during the pandemic derived mainly from hotel, restaurant, and entertainment taxes rather than destination retribution.Conclusions: Strategy formulation was sound in direction but structurally disconnected from direct PAD generation, while budget constraints, human resource deficits, low community awareness, and Cyclone Seroja compounded the pandemic’s impact.Limitations: The single-city scope, small government-only informant pool, and subjective SWOT weighting restrict the generalisability of findings to other secondary cities in Eastern Indonesia.Contributions: The study extends destination-level SWOT applications in Eastern Indonesia by linking strategic positioning explicitly to fiscal outcomes, offering local governments an evidence-based framework for aligning tourism strategy formulation with revenue mobilisation objectives under crisis conditions, and for distinguishing programme activity from measurable fiscal return.